Refleksi Penelitian Budaya Kerja Pada Instansi Pemerintahan - Sammy Rifah Sihombing; Khairul Ikhwan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Organizational culture is a link between members, so an organization must have a strong culture, aligned commitments and shared beliefs to increase its global competitiveness. The purpose of this study is to provide an overview or description of the development of organizational culture research in Indonesia. The method used is a literature study related to the field mapping method (Hesford et al., 2007). In this study, articles are organized based on topic, research method, and research field. The most studied dependent variable is employee performance, the most studied independent variable is organizational culture. The research method uses a qualitative method in the form of a literature review of previous studies.